Biomechanical analysis of dual versus lateral locked plating in elderly bicondylar tibial plateau fractures: Does medial comminution matter?. Issue 10 (October 2022) - García Vélez, Dencel A.; Headford, Mikel; Suresh, Krishna Vangipuram; Liberatos, Paraskevi Marousa; Bledsoe, Gary; Revak, Thomas
Abstract: Objective: To assess dual plating versus lateral locked plate fixation of bicondylar tibial plateau fractures in an elderly cadaveric model with and without medial bone loss Participants: 10 pairs of elderly (range 78–93 years of age) fresh frozen tibias. Intervention: Bicondylar tibial plateau fractures were created reproducing AO/OTA 41 C1 (without medial bone loss) and C2 fractures (with medial bone loss). Cadavers were randomized to 4 different groups. Groups 1 and 2 were 41 C1 fractures and fixated with either dual or lateral plating, respectively. Groups 3 and 4 were fixated in a similar fashion with medial metaphyseal bone loss (41 C2 fracture) with dual plating Group 3 and lateral plating group 4. Lateral plating consisted of a 3.5 mm 5-hole lateral plate (ALPS, ZimmerBiomet) with 6 bicortical locking screws proximally and two diaphyseal screws. Dual plating groups underwent lateral plating and additional 3.5 mm 5-hole posteromedial 1/3 tubular plate (ZimmerBiomet) placed at the apex of the fracture with two shaft screws and one unicortical screw proximally. Specimens were tested in a Mechanical Testing System (MTS) machine loading both condyles. Outcome measurements: Specimens were loaded to 300 N and coronal alignment obtained. Specimens were then cycled from 100 N to 700 N for 5000 cycles at 2 Hz. Average axial displacement, maximal displacement, average force and coronal alignment after 5000 cycles were recorded. Lastly, force to failure was recorded at 100 N/sec. Results: Mean axial displacement was 4.21 mm ranging from 3.12 mm in group 1 to 5.92 mm in group 4 ( P = 0.51). Failure force averaged 3340 N ranging from 4342 N in group 1 to 2433 N in group 4 ( P = 0.36). Maximal displacement ranged from 3.69 mm in group 1 to 7.37 mm in group 4 ( P = 0.21). Change in coronal alignment ranged from 0.98° in group 1 to 1.97° in group 4 ( P = 0.45). No statistically significant difference was noted between all four groups for all data points. Conclusion: The results of this study demonstrate that a lateral locked plate may offer an alternative means of fixation in AO/OTA 41 C1 and C2 fractures.